Track student attendance at a time of the COVID-19 pandemic using location-finding technology - Jusoh J.A.; Nazari Mohd Rose A.; Aledinat L.S.; Altrad A.; Ahmad Saany S.I.; Aseh K.; Mohamed R.R.; Ravindran Pathmanathan P.; Baker El-Ebiary Y.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer aided instruction; E-learning; Electronic document exchange; Global positioning system; Learning systems; Ubiquitous computing; Websites; Application frameworks; Open distance learning; Student attendances; Student engagement; Student participation; Time synchronization; Triangulation techniques; Web based learning; Students